Förslag på utformning av grundläggande laddinfrastruktur för elfordon i Luleå - Söderlund, Björn (2015)
The energy company Luleå Energi wants to examine the need for public charging for electric cars in the municipality of Luleå and wants to know how to design a charging infrastructure. The aim of this project was to support the company in matters concerning charging infrastructure. The goal was to develop a recommendation on how to design a basic public infrastructure for charging electric cars in Luleå. The thesis work is based on a literature study and dialogue with various professionals with knowledge about charging infrastructure and the use of electric cars.Electric cars are mainly charged overnight in connection to the residency, or during the day at the work place. However, due to today’s vehicles' limited range, a certain public charging infrastructure is needed in order to increase the effective range. Public charging stations are also needed to allow longer trips with battery electric vehicles and to enable plug-in hybrids to be predominantly powered by electricity. Normal power recharging points can recharge an electric vehicle battery in one to six hours. These units should be positioned at well-attended parking spaces where vehicles are parked for a longer period of time, for example in the city center, at shopping centers and airports. High power recharging points will typically recharge an electric car battery in 20 to 30 minutes. These charging stations should primarily be located along freeways and highways, at fuel stations or similar facilities.The report includes recommendations for charging power, connector types and communication systems that will ensure a user-friendly charging infrastructure that is well- prepared for future needs. Normal charging stations that are established in Luleå should have fixed cables and should be equipped with Type 1 and Type 2 connectors. High power charging stations are always fitted with fixed cables and should be equipped with CHAdeMO and Combo 2 connectors. In order for users to retrieve status information through navigation systems or online map ...